Inflation Dynamics and the Labour Share in the UK - Nicoletta Batini; Brian Jackson; Stephen Nickell (Bank of England, External Monetary Policy Committee Unit, 2000)
In recent years UK real wages have been growing faster than labour factor productivity, implying that the labour share has been rising. This paper looks at various definitions of the labour share and derives a measure for the UK, which appears positively correlated with the growth rate of the UK gross value added price deflator. Following Layard, Nickell and Jackman (1991), we investigate the relationship between inflation and the share more formally by estimating a pricing equation or "new Phillips curve" obtained from a structural dynamic model of price setting based on Rotemberg (1982) and extended to capture employment adjustment costs and the openness of the UK economy. This model nests the Sbordone (1998) and Gali, Gertler and Lopez-Salido (2000) relationship between inflation and marginal costs in the limiting case of a constant equilibrium mark-up and no employment adjustment costs. Our findings suggest that there is a stable ceteris paribus relationship between inflation and the labour share over the last 30 years in the UK and so the share contains information that helps to predict inflation.
Keywords: 330